Diagnosis dan penanganan rehabilitasi medik pada anak dengan Attention Deficit Hyperactivity Disorder - Susanto, Bayu D.; Sengkey, Lidwina S. (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: Attention deficit hyperactivity disorder (ADHD) is one of the most common childhood disorders and can continue through adolescence and adulthood. The average age of onset is 7 years old. Symptoms in children is characteriterized by inattention, hyperactivity and impulsivity, or a combination of these symptoms, which compromise basic daily functions such as learning to read and making friends. ADHD is a complex disorder of impairment of brain functions, associated with low rates of high-school graduation and completion of postsecondary education as well as poor peer relationships, even when it is appropriately managed, leading to high economic and social burdens. In many cases, it is accompanied by one or more serious psychiatric comorbidities. In practice, the diagnosis is often made in children who meet some but not all of the criteria recommended in DSM-IV. According to National Institute of Mental Health and professional organizations such as AACAP, the management of children with ADHD is a comprehensive, multidisciplinary and multimodal approach. The managerial team of children with ADHD involves medical rehabilitation specialists, physiatrists with occupational therapiests, psychologists, social workers, parents, teachers, care givers, and environment.Keywords: ADHD, inattention, hyperactivity, impulsivity, rehabilitation medicineAbstrak: Attention deficit hyperactivity disorder (ADHD) adalah adanya pola menetap dari inatensi yang disertai hiperaktifitas dan impulsivitas, umumnya terjadi pada anak usia dini dan usia sekolah. Gejala dapat diketahui sebelum usia 7 tahun dan dapat menetap sampai masa remaja dan dewasa. ADHD dapat mengganggu fungsi dasar seorang anak, permasalahan dalam hal belajar, dan kesulitan membina hubungan dengan teman. ADHD merupakan gangguan yang kompleks dari fungsi otak yang menimbulkan masalah dalam pendidikan dan sosial serta membutuhkan biaya yang cukup besar. Pada banyak kasus disertai oleh 1 atau lebih masalah psikiatri yang serius. Kriteria diagnosis didasarkan pada Diagnostic and Statistic Manual IV (DSM-IV). Sampai saat ini belum ada satu jenis terapi yang dapat diakui untuk menyembuhkan anak dengan ADHD secara total. Berdasarkan National Institute of Mental Health serta organisasi profesi lainnya di dunia seperti AACAP penanganan anak dengan ADHD ialah dengan pendekatan komprehensif yang multidisiplin dan multimodal. Penanganan pada anak dengan ADHD melibatkan multidisipliner ilmu termasuk dokter spesialis kedokteran fisik dan rehabilitasi bersama tim termasuk psikolog, okupasi terapi, sosial medik, orang tua, guru, care giver dan lingkungan.Kata kunci: ADHD, inattention, hyperactivity, impulsivity, rehabilitation medicine